Non-invasive in vivo imaging of porcine islet xenografts in a preclinical model with [68Ga]Ga-exendin-4 - Lindheimer, Felix; Lindner, Magdalena Julia; Oos, Rosel; Honarpisheh, Mohsen; Zhang, Yichen; Lei, Yutian; Wolf-van Buerck, Lelia; Gildehaus, Franz Josef; Lindner, Simon; Bartenstein, Peter; Kemter, Elisabeth; Wolf, Eckhard; et al. (Frontiers in Nuclear Medicine, 2023)
Background: Islet xenotransplantation may be a therapeutic option in type 1 diabetes. Recent advances in generating genetically modified source pigs offer advantages as immune suppressants can potentially be eliminated after the transplantation. Therapy monitoring would greatly benefit from noninvasive methods for assessing the viability of transplanted islets. Peptide-based positron emission tomography (PET) targeting the glucagon-like peptide-1 receptor (GLP1R) expression on beta cells may offer a procedure that can directly be translated from an experimental setting to the clinic. The aim of this study was to establish the labeling of the GLP1R ligand [68Ga]Ga-exendin-4, to demonstrate the feasibility to image porcine islet xenografts in vivo, and to compare signal quality for three different transplantation sites in a mouse model. Methods: Mice with engrafted neonatal porcine islet cell clusters (NPICCs) under the kidney capsule, into the inguinal fold, or the lower hindlimb muscle were studied. After reaching normoglycemia, the mice were injected with [68Ga]Ga-exendin-4 for PET data acquisition. Subsequent autoradiography (AR) was used for comparing ex vivo data with in vivo uptake. Results: NPICCs in the lower right hindlimb muscle could be detected in vivo and in AR. Due to the high background in kidney and urinary bladder, islets could not be detected in the PET data at transplantation sites close to these organs, while AR showed a clear signal for the islets in the inguinal fold. Conclusion: PET with [68Ga]Ga-exendin-4 detects islets transplanted in the hindlimb muscle tissue of mice, offering the potential of longitudinal monitoring of viable porcine islets. Other sites are not suitable for in vivo imaging owing to high activity accumulation of Exendin-4 in kidney and bladder.